2013
DOI: 10.1111/ina.12053
|View full text |Cite
|
Sign up to set email alerts
|

Stability of airborne microbes in the Louvre Museum over time

Abstract: The microbial content of air has as yet been little described, despite its public health implications, and there remains a lack of environmental microbial data on airborne microflora in enclosed spaces. In this context, the aim of this study was to characterize the diversity and dynamics of airborne microorganisms in the Louvre Museum using high-throughput molecular tools and to underline the microbial signature of indoor air in this human-occupied environment. This microbial community was monitored for 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 51 publications
3
22
0
1
Order By: Relevance
“…These can arise from faulty air conditioning systems, from the presence of people, who represent one of the major carriers of microorganisms, and from sources that are in direct contact with the external environment, such as entrances and exits, or windows or doors (Orlandi et al, 2011;Quian et al, 2012;Gauzere et al, 2014). These airborne particles can be deposited on the works of art, and under favourable conditions of temperature, humidity, light and substrate, they can use the different surfaces not just as a physical support for their growth, but also as a nutrient source.…”
Section: Introductionmentioning
confidence: 99%
“…These can arise from faulty air conditioning systems, from the presence of people, who represent one of the major carriers of microorganisms, and from sources that are in direct contact with the external environment, such as entrances and exits, or windows or doors (Orlandi et al, 2011;Quian et al, 2012;Gauzere et al, 2014). These airborne particles can be deposited on the works of art, and under favourable conditions of temperature, humidity, light and substrate, they can use the different surfaces not just as a physical support for their growth, but also as a nutrient source.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been performed to determine the characteristics and sources of particulate matter and airborne microorganisms inside museums [2,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Gaüzère et al [134] applied CE-SSCP and other high throughput molecular methods to study the microorganism distribution of indoor air. They found that the bacterial diversity in indoor airborn is stable, whereas the corresponding eukaryote group is unstable.…”
Section: Simultaneously Detecting Multiple Types Of Pathogensmentioning
confidence: 99%
“…The core species belong primarily to the Proteobacteria and Actinobacteria, and to the genera Paracoccus spp, Acinetobacter sp., Pseudomonas sp., Enhydrobacter sp., Sphingomonas sp., Staphylococcus sp., and Streptococcus sp. [134].…”
Section: Simultaneously Detecting Multiple Types Of Pathogensmentioning
confidence: 99%